The abandonment of elderly women in the Covid-19 pandemic: A look from health professionals (Research, Society and Development, 2023)
The present study aimed to understand the situation of abandonment of elderly women in the context of the Covid-19 pandemic, from the perspective of health professionals, in a reference unit in health care for the elderly. This is a qualitative study, whose data collection was carried out through semi-structured interviews with twelve health professionals, who work in a health care unit, located in the city of Rio de Janeiro-RJ. Data analysis was constructed using the hybrid Hermeneutic-dialectic method. It was possible to identify that professionals understand what abandonment is experienced by the elderly, as well as know how to identify it. This perception usually happens through home visits. However, it is also observed the difficulty of the interviewees in understanding the problem beyond what is possible to visualize in these visits or what is narrated by the relatives and/or neighbors of the elderly woman. The team's effort in articulating with the available equipment is notorious, however, the neglect of the public power with the systems of care for the elderly makes it difficult to care for and guarantee the rights of these subjects. There was an increase in abandonment, in the context of the pandemic. However, the scenario experienced by the subjects allowed greater visibility to this problem. The results lead to further studies in depth, through expansion to other territories in the city of Rio de Janeiro.